SUMIDA, PENGALAMAN TATAKELOLA SUNGAI YANG MENGINSPIRASI - Murtedjo, Tedy; Purba, Aleksander (UNIVERSITAS LAMPUNG, 2012)
The Sumida River (Sumida-gawa) is a river which flows through Tokyo Japan. It branches fromthe Arakawa River at Iwabuchi and flows into Tokyo Bay. Its tributaries include the Kanda andShakujii rivers. What is now known as the